66.5k views
4 votes
How do I solve 4(x+3)-(x-1)=40

2 Answers

0 votes

The answer is: x = 9

Here's how I got my answer:

Step 1: Simplify the brackets. Which leaves us with
4(x+3)-x+1=40

Step 2: Expand it. Which leaves us with
4x+12-x+1=40

Step 3: Simplify
4x+12-x+1 to
3x+13. Which leaves us with
3x+13=40

Step 4: Subtract 13 from both sides. Which leaves us with
3x=40-13

Step 5: Simplify
40-13 to 27. Which leaves us with
3x = 27

Step 6: Divide both sides by 3, leaving us with our answer, x = 9.

User Sergey Tyupaev
by
5.7k points
4 votes


4(x+3)-(x-1)=40\\\\ 4x+12-x+1=40\\\\ 3x=27\\\\ x=9

User Geo
by
5.1k points